Karya Karawitan Inovatif “Dancing in The Storm” - I Gede Esa Supartha; Ni Ketut Dewi Yulianti; I Nyoman Mariyana (Institut Seni Indonesia Denpasar, 2023)
Purpose: Human life has various kinds of unexpected things in it, just like lightning that can appear without waiting for rain to arrive. Lightning occurs because there is a potential difference between the cloud and the earth. The process of charge occurring in the cloud is due to its continuous, regular movement, and during that movement it will interact with other clouds so that negative charges will gather on one side, and positive charges on the other side. The purpose of creating this innovative karawitan work is to transform ideas that are born from natural phenomena, namely lightning, and to describe the values contained in the innovative karawitan work Dancing In The Storm. Method: The creation of the work